Feasibility of autologous plasma gel for tonsil-derived stem cell therapeutics in hypoparathyroidism - Jung, Soo Yeon (Sci Rep, 2018)
Hypoparathyroidism is a deficiency of the parathyroid hormone (PTH) in the body. We previously reported the possibility of treating it using tonsil-derived mesenchymal stem cells (TMSCs) differentiated into PTH-releasing cells. The purpose of this study was to evaluate the feasibility of using autologous plasma gel as scaffold material in treatment of hypoparathyroidism with TMSC. We obtained plasma by venous sampling of autologous blood and centrifuged and fabricated the plasma gel using a sinusoidal pattern heating machine. After we created the hypoparathyroidism animal model, we administered undifferentiated TMSCs and TMSCs differentiated into parathyroid cells at each rat dorsum by intramuscular injection with and without the plasma gel. In the plasma gel groups, intact PTH was detected from on day 21 after TMSC injection; we did not detect intact PTH in the groups that were only transplanted with TMSCs during the entire experimental period. Serum calcium was higher and phosphorous was lower in the TMSC with plasma gel groups than in the groups with TMSCs alone. We detected PTH and chromogranin A in the TMSC-plasma gel-transplanted areas on immunohistochemistry and immunofluorescence stain. Plasma gel can be considered as a cell-delivery scaffold for treating hypoparathyroidism with tonsil-derived mesenchymal stem cells.